IPTEKS SISTEM INFORMASI MANAJEMEN DAERAH KEUANGAN PADA BADAN PERENCANAAN, PENELITIAN DAN PENGEMBANGAN DAERAH (BAPELITBANGDA) KOTA MANADO - Wantah, Kezia; Lintong, Diana (Universitas Sam Ratulangi, 2018)
The Regional Planning, Research and Development Agency (BAPELITBANGDA) of Manado City is a regional work unit that has the task of assisting the Mayor in determining policies in the area of development planning in the region as well as evaluating and implementing them. To facilitate financial management in local government organizations, BAPELITBANGDA implements SIMDA in its financial management system. SIMDA Finance is an application program developed by the Financial and Development Supervisory Agency (BPKP), where the purpose of developing SIMDA applications is to accelerate the process of regional financial management. The SIMDA Financial application to BAPELITBANGDA has helped in managing and administering its financial data. Keywords : Implementation of SIMDA, Financial SIMDA